CRISIS MANAGEMENT STRATEGIES AND ENTREPRENEURIAL RESILIENCE OF TOURISM BUSINESS OPERATORS IN JAKARTA AMID COVID-19 - Libraveda, Lesca Terlly; Tampubolon, Lamtiur Hasianna; Prasadja, Heru (International Journal of Research -GRANTHAALAYAH, 2023)
The tourism and creative economy sectors in Indonesia have undergone notable growth over recent years, playing a pivotal role in bolstering the nation's revenue and contributing to the advancement of communities across the country. Jakarta, as the nation’s capital and the economic center, serves as the primary entry point for international tourists, supporting the overall growth of the tourism industry. Soekarno-Hatta Airport, aside from being an international aviation hub, facilitates access to various tourist destinations across Indonesia. The emergence of Covid-19 has triggered a global crisis and greatly disrupted the world economy. The WHO's declaration of a health emergency led to the implementation of multiple virus control measures, including lockdowns, social distancing protocols, and travel restrictions. Consequently, the tourism sector which heavily reliant on human mobility, experienced severe setbacks and become one of the hardest-hit industry. To endure such crises, businesses are required to adapt swiftly and adopt an entrepreneurial perspective to meet consumer needs amid uncertainty. This research aims to investigate the strategies for crisis management and the application of entrepreneurial resilience among Jakarta's tourism business operators in response to the Covid-19 pandemic. The study employs qualitative descriptive approaches, using semi-structured interviews and documentary analysis as data collection techniques. Interviews were conducted with stakeholders in the tour and travel and hospitality industry. Findings indicate that not all businesses have crisis mitigation procedures for the unexpected threats. Businesses are responding to this crisis by adapting, innovating, and seizing every opportunity to ensure their survivals.